Особливості автоматизованого керування режимами випікання хлібної продукції - Іващук, В. В.; Ладанюк, А. П. (Видавництво Львівської політехніки, 2011)
Presented results of the control system of technological modes baking bread blanks in the deadlock type oven with forced convection of heat flow.
Keywords: temperature-steam mode; deadlock type oven; discrete control; steam processing; stress of heat in oven; forced convection